Left ventricular remodeling following aortic root and ascending aneurysm repair - Houben, Ignas B.; Chu, Angel K. Y.; Yang, Bo; Kim, Karen M.; Fukuhara, Shinichi; van Herwaarden, Joost A.; Moll, Frans L.; Nordsletten, David A.; Figueroa, C. Alberto; Burris, Nicholas S.; Patel, Himanshu J. (Frontiers in Cardiovascular Medicine, 2022)
Objective Adverse left ventricular remodeling due to a mismatch between stiffness of native aortic tissue and current polyester grafts may be under-recognized. This study was conducted to evaluate the impact of proximal aortic replacement on adverse remodeling of the left ventricle. Materials and methods All aortic root and ascending aortic aneurysm patients were identified (n = 2,001, 2006–2019). The study cohort consisted of a subset of patients (n = 98) with two or more electrocardiogram (ECG)-gated CT angiograms, but without concomitant aortic valve disease or bicuspid aortic valve, connective tissue disease, acute aortic syndrome or prior history of aortic repair or mitral valve surgery. LV myocardial mass was measured from CT data and indexed to body surface area (LVMI). The study cohort was divided into a surgery group (n = 47) and a control group; optimal medical therapy group (OMT, n = 51). Results The mean age was 60 ± 11 years (80% male). Beta-blocker use was significantly more frequent in the surgery group (89 vs. 57%, p < 0.001), whereas, all other antihypertensive drugs were more frequent in the OMT group. The average follow-up was 9.1 ± 4.0 months for the surgery group and 13.7 ± 6.3 months for the OMT group. Average LVMI at baseline was similar in both groups (p = 0.934). LVMI increased significantly in the surgery group compared to the OMT group (3.7 ± 4.1 vs. 0.6 ± 4.4 g/m2, p = 0.001). Surgery, baseline LVMI, age, and sex were found to be independent predictors of LVMI increased on multivariable analysis. Conclusion Proximal aortic repair with stiff polyester grafts was associated with increased LV mass in the first-year post-operative and may promote long-term adverse cardiac remodeling. Further studies should be considered to evaluate the competing effects of aortic aneurysm related mortality against risks of long-term graft induced aortic stiffening and the potential implications on current size thresholds for intervention.